Piety, Social Pressure, and Riya’: Religious Practices of Yogyakarta Urban Muslim Youth in Digital Media - Achfandhy, Mochammad Irfan; Rohmatulloh, Dawam Multazamy (UIN Sayyid Ali Rahmatullah Tulungagung, Indonesia, 2024)
This article examines the relationship between piety, social pressure, and riya’ among urban Muslim youth in Yogyakarta who use social media to express religiousity, and the way the youth negotiate to deal with the contradiction between displayed piousness and religious norms. Employing a phenomenological approach this article explore the negotiation of ambiguity among urban Muslim youth, in particular the urban students actively involved in lecture series branded